Figure 5 in New contributions to the marine benthic ciliates from the Antarctic area, including description of seven new species (Protozoa, Ciliophora) - Wilbert, Norbert; Song, Weibo (Zenodo, 2005)
Figure 5. (A–C) Intranstylum antarcticum nov. spec. and (D–F) Telotrochidium sp. from life (A–C) and protargol impregnation (D–F). (A) Typical specimen, arrow marks the peristomelipe, double-arrowheads mark the reduced spasmoneme; (B) portion of stalk, arrow marks the myoneme, note the place where the myoneme is broken (arrowhead); double-arrowheads indicate the bacteria attached to the stalk; (C) to show the general stalk arrangement; (D) general view, to show the macronucleus (arrow) and infraciliature; (E) detailed part of aboral ciliary wreath; (F) buccal apparatus, arrow marks the peniculus 3, arrowhead indicates the haplokinety, doublearrowheads point to the epistomial membrane. Scale bars: 50 Mm (A); 200 Mm (C); 30 Mm (D). Published as part of Wilbert, Norbert & Song, Weibo, 2005, New contributions to the marine benthic ciliates from the Antarctic area, including description of seven new species (Protozoa, Ciliophora), pp. 935-973 in Journal of Natural History 39 (13) on page 948, DOI:10.1080/00222930400001509, http://zenodo.org/record/4657793